2002
DOI: 10.4028/www.scientific.net/msf.396-402.1671
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue of Friction Stir Welded 2024-T351 Aluminium Alloy

Abstract: Abstract. Fatigue failure characteristics of friction stir welds in 13mm gauge 2024-T351 plate have been assessed. Failure occurred from either the weld region (nugget/flow arm) or from the material immediately surrounding the weld. Fatigue failure from the surrounding material was essentially conventional, initiating from large S-phase intermetallic particles and growing in a macroscopic mode I manner. Corresponding fatigue lives were seen to be comparable to parent plate and results previously reported for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 4 publications
(6 reference statements)
2
11
0
Order By: Relevance
“…Booth and Sinclair (Ref. 17) found that fatigue failures in the nugget region appear to compromise fatigue life, and that coupons that failed outside of the nugget area were comparable with published parent material data. The failures that occurred in the nugget were "related to the presence of macroscopic discontinuities in the flow pattern of the flow arm," which they showed to have differences in hardness values between the bands.…”
Section: Weld Flaws and Defectssupporting
confidence: 68%
“…Booth and Sinclair (Ref. 17) found that fatigue failures in the nugget region appear to compromise fatigue life, and that coupons that failed outside of the nugget area were comparable with published parent material data. The failures that occurred in the nugget were "related to the presence of macroscopic discontinuities in the flow pattern of the flow arm," which they showed to have differences in hardness values between the bands.…”
Section: Weld Flaws and Defectssupporting
confidence: 68%
“…Booth and Sinclair [107] asserted that fatigue failure in FSW 2024-T351 could occur within the weld nugget or at the HAZs (i.e HAZ or TMAZ). Failure in the nugget was linked to discontinuities in the material flow pattern at the surface in the absence of obvious defects.…”
Section: Fractography Of the Surfaces Of Fsw Failed Specimensmentioning
confidence: 99%
“…These differences in hardness value within the nugget have been correlated with the size of the precipitates present in the region (Ref [12][13][14][15]. The 2xxx and 7xxx show the hardness minima within the TMAZ zone (Ref 6,9,16,17). The effect has been attributed to over-aging (Ref 12).…”
Section: Introductionmentioning
confidence: 94%